2021
DOI: 10.1002/chem.202103287
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐ and Copper‐Catalyzed Propargylic Substitution Reactions of Propargylic Alcohol Derivatives with Hydrazones

Abstract: Ruthenium-and copper-catalyzed propargylic substitution reactions of propargylic alcohol derivatives with Nmonosubstituted hydrazones as ambident nucleophiles are achieved in which N-monosubstituted hydrazones exhibit impressive different reactivities depending on different catalytic systems, behaving as carbon-centered nucleophiles to give the corresponding propargylic alkylated products in ruthenium catalysis, or as nitrogen-centered nucleophiles to afford the corresponding propargylic aminated products in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
1
3
0
Order By: Relevance
“…( S )‐1‐(Benzo[ b ]thiophen‐3‐yl)prop‐2‐yn‐1‐ol [( S )‐1 c] : ( S )‐ 1 c was obtained by the general procedure and purified by flash column chromatography using hexane/EtOAc (4 : 1) as an eluant; 97 % yield (24 mg); a yellow solid; Mp 64–65 °C; its enantiomeric excess was determined by HPLC analysis at 20 °C using a CHIRALPAK IA‐3 column (hexane/propan‐2‐ol (90 : 10), 1 mL/min, UV detection 220 nm, t R =11.0 min ( S ), 9.5 min ( R )); [α] 22D ${{{22\hfill \atop {\rm D}\hfill}}}$ =+39 ( c 0.38, CHCl 3 ); 1 H NMR (500 MHz, CDCl 3 ): δ =8.03 (d, J =7.5 Hz, 1H), 7.87 (d, J =7.5 Hz, 1H), 7.68 (s, 1H), 7.43 (td, J =7.5, 1.0 Hz, 1H), 7.39 (td, J =7.5, 1.0 Hz, 1H), 5.80 (dd, J =7.0, 2.0 Hz, 1H), 2.72 (d, J =2.0 Hz, 1H), 2.25 (d, J =7.0 Hz, 1H); 13 C NMR (125 MHz, CDCl 3 ): δ =141.0, 136.6, 134.6, 125.0, 124.7, 124.3, 122.9, 122.5, 82.5, 74.6, 59.9. 1 H and 13 C NMR data of the product ( S )‐ 1 c were in agreement with (±)‐ 1 c in the literature [25] …”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…( S )‐1‐(Benzo[ b ]thiophen‐3‐yl)prop‐2‐yn‐1‐ol [( S )‐1 c] : ( S )‐ 1 c was obtained by the general procedure and purified by flash column chromatography using hexane/EtOAc (4 : 1) as an eluant; 97 % yield (24 mg); a yellow solid; Mp 64–65 °C; its enantiomeric excess was determined by HPLC analysis at 20 °C using a CHIRALPAK IA‐3 column (hexane/propan‐2‐ol (90 : 10), 1 mL/min, UV detection 220 nm, t R =11.0 min ( S ), 9.5 min ( R )); [α] 22D ${{{22\hfill \atop {\rm D}\hfill}}}$ =+39 ( c 0.38, CHCl 3 ); 1 H NMR (500 MHz, CDCl 3 ): δ =8.03 (d, J =7.5 Hz, 1H), 7.87 (d, J =7.5 Hz, 1H), 7.68 (s, 1H), 7.43 (td, J =7.5, 1.0 Hz, 1H), 7.39 (td, J =7.5, 1.0 Hz, 1H), 5.80 (dd, J =7.0, 2.0 Hz, 1H), 2.72 (d, J =2.0 Hz, 1H), 2.25 (d, J =7.0 Hz, 1H); 13 C NMR (125 MHz, CDCl 3 ): δ =141.0, 136.6, 134.6, 125.0, 124.7, 124.3, 122.9, 122.5, 82.5, 74.6, 59.9. 1 H and 13 C NMR data of the product ( S )‐ 1 c were in agreement with (±)‐ 1 c in the literature [25] …”
Section: Methodssupporting
confidence: 88%
“…1 H and 13 C NMR data of the product (S)-1 c were in agreement with (�)-1 c in the literature. [25] ( 9, 147.8, 134.0, 120.3, 108.2, 107.3, 101.2, 83.4, 74.8, 64.2. 1 H and 13 C NMR data of the product (S)-1 d were in agreement with (�)-1 d in the literature.…”
Section: (S)-1-(thiophen-3-yl)prop-2-yn-1-ol [(S)-1 A]mentioning
confidence: 99%
“…This radical coordinated with the metal to deliver radical-metal In 2021, Sakata and Nishibayashi et al employed ruthenium and copper catalysts in the reaction of propargylic alcohols 1' with N-monosubstituted hydrazones 152 (Scheme 65). [62] In the ruthenium catalysis system, hydrazone substrates acted as carbon-centered nucleophiles, whereas they showed nitrogen-centered nucleophilicity behavior in the presence of a copper catalyst. DFT calculations and study of Gibbs free energies of intermediates showed that in the Rucatalyzed reaction, [1,6]-H shift was preferred in the C-attack pathway and alkylated products were observed.…”
Section: Reaction With C Nucleophilesmentioning
confidence: 99%
“…Propargyl alcohols are ubiquitous building blocks in chemical synthesis, being highly valued for their widespread application as valuable synthetic intermediates or medicinally relevant molecules themselves. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] They participate in a diverse array of transformations, owing this to their multifunctionality, and thereby being the subject of numerous studies. Protected propargyl alcohols can be accessed via well-developed stoichiometric methods, including mainly the use of a combination of propargyl alcohol, chlorosilane and organolithium reagent (Fig.…”
Section: Introductionmentioning
confidence: 99%